SOEGIJA BIOPIC FILM, POLITICAL AFIRMATION, AND POLITICAL IDENTITY: DECONSTRUCTION OF INDONESIAN HISTORIOGRAPHY - Kartika, Bambang Aris; Prihatini, Nanik Sri; Hastanto, Sri; Dharsono, Dharsono (Seni Media Rekam ISI Surakarta, 2020)
Soegija's movie is a biopic film based on the historiography of the highest leaders of the people and the Catholic church in Indonesia. Soegija's film is an antithesis of Indonesian historiography so far, especially the historiography of the era of the Indonesian independence revolution. This article discusses the political affirmation and identity politics of Soegija's film from the perspective of Derrida's Deconstruction. Derrida's Deconstruction approach and historical methodology consisting of Heuristics, Hermeneutics, and internal criticism are used to understand the position of Soegija's biopic on Indonesian historiography. The results of the study show that Soegija's film is a biography moving picture of the character Mgr. Albertus Soegijapranata, who narrated historical facts about the national attitude of the Catholic leadership as the first native bishop. In deconstruction, it appears that Soegija's biopic is a representation of the political affirmation and identity politics of educational cultural resistance to the truth of the historical facts of the character Mgr. Albertus Soegijapranata who is in binary opposition to Indonesian historiography.